Elucidation of the structural and optical properties of metal cation (Na+, K+, and Bi3+) incorporated Cs2AgInCl6 double perovskite nanocrystals. Issue 7 (20th January 2022) - Vashishtha, Parth; Griffith, Benjamin E.; Fang, Yanan; Jaiswal, Ankit; Nutan, Gautam V.; Bartók, Albert P.; White, Tim; Hanna, John V.
Abstract : Potassium substituted double perovskite nanocrystals of the form Cs2 K x Ag1− x InCl6 :Bi ( x = 0–1) exhibit improved PLQY behaviour and structural diversity. Abstract : This study presents series of direct band gap Pb-free double perovskite Cs2 AgIn x Bi1− x Cl6, Cs2 Na x Ag1− x InCl6 :Bi and Cs2 K x Ag1− x InCl6 :Bi nanocrystal systems [Cs2 B′(I)B′′(III)Cl6 ] synthesised using a colloidal hot-injection route. The structural properties investigated using powder XRD, TEM, solid state NMR and materials modelling approaches demonstrate that the incorporation of K + cations into the double perovskite nanocrystal structure occurs simultaneously on both the Cs (A) site and Ag (B′(I)) positions within a series of closely related cubic and monoclinic structures. As a result of defect passivation, significant improvements in the photoluminescence quantum yield (PLQY) of ∼4.7× and ∼1.8× are exhibited in comparison to the Cs2 AgIn x Bi1− x Cl6, and Cs2 Na x Ag1− x InCl6 :Bi nanocrystal systems, respectively. Materials modelling using the Ab Initio Random Structure Search (AIRSS) method, and the GIPAW DFT calculation of the NMR parameters from the derived structural realisations, shows that K + incorporation induces significant short-range structural disorder and multi-phase formation. This is highlighted by the large 133 Cs and 39 K chemical shift dispersion characterising the MAS NMR data. Density of States (DoS) calculations describing these AIRSS generated structures suggest that increasing ionic character and reduced structural rigidity are strongly correlated with A site substitution of the K + cation into these cubic and monoclinic phases. The 39 K MAS NMR data reveals that the increasing PLQY performance maps directly with the K + incorporation into the cubic CsK y Ag1− y InCl6 phase supporting B site occupancy which is observed to be maximized at a 60 ml% K + incorporation level. However, additional evidence indicates that low level K + substitution primarily targets A site occupancy in a surface passivation role. The improvement to the optical properties induced by K + and Na + incorporation is rationalised in terms of increased covalent character and structural rigidity associated with decreased Cs +, Na + and K + cation mobility, as evidenced by the large (∼2 orders of magnitude) variation in the 133 Cs T 1 data across each compositional range.